PENGARUH GREEN KNOWLEDGE, GREEN ENVIRONMENTAL CONCERN TERHADAP GREEN ATTITUDE DAN GREEN PURCHASE INTENTION PADA GENERASI Z DI KOTA PEKANBARU - Ramadani Safitri; Restuti Sri; Jushermi Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Today's increasing public awareness, about how important it is to maintainenvironmental sustainability, has made many producers of various products begin toswitch to using materials that do not damage the environment or the term isenvironmentally friendly materials. One example is to preserve the environment and toprotect our earth today we need to choose from now on the products we will use. Withthat, it is necessary to start from the youth as the originator, namely Generation Z whowill start choosing products that are environmentally friendly. This study aims todetermine how much influence Green Knowledge, Green Environmental Concern has onGreen Attitude and Green Purchase Intention to Generation Z in Pekanbaru city.Primary data were collected using a questionnaire as an instrument and structuredinterviews were used as a complement in proving the results of the study. This study uses112 Generation Z in Pekanbaru City who intend to make purchases on environmentallyfriendly products as respondents with the Non-Probability Sampling technique. Themethod used is Explanatory Research with data analysis test, classical assumption test,hypothesis test, and path analysis as a data testing flow and assisted by SPSS applicationin terms of data processing. The results of this study indicate that: (1) Green Knowledgehas a positive and significant effect on Green Attitude (2) Green Environmental Concernhas a positive and significant effect on Green Attitude (3) Green Knowledge has apositive and significant effect on Green Purchase Intention (4) Green EnvironmentalConcern positive and significant effect on Green Purchase Intention Green Attitude haspositive and significant effect on Green Purchase Intention (5) Green Knowledge haspositive and significant effect on Green Purchase Intention through Green Attitude (7)Green Environmental Concern has positive and significant effect on Green PurchaseIntention through Green Attitude. Keywords: Green Knowledge, Green Environmental Concern, Green Attitude, GreenPurchase Intention, Generation Z